2017
DOI: 10.1080/09168451.2017.1387049
|View full text |Cite
|
Sign up to set email alerts
|

CE–MS-based metabolomics reveals the metabolic profile of maitake mushroom (Grifola frondosa) strains with different cultivation characteristics

Abstract: Maitake mushroom (Grifola frondosa [Dicks.] Gray) is generally cultured using the sawdust of broadleaf trees. The maitake strain Gf433 has high production efficiency, with high-quality of fruiting bodies even when 30% of the birch sawdust on the basal substrate is replaced with conifer sawdust. We performed metabolome analysis to investigate the effect of different cultivation components on the metabolism of Gf433 and Mori52 by performing CE-MS on their fruiting bodies in different cultivation conditions to qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 31 publications
(33 reference statements)
0
8
0
Order By: Relevance
“…Metabolic profiling was performed on rodent muscle , heart , liver , brain , intestinal and glioma tissue, arterial cells as well as on rodent serum/plasma , urine and feces . CE‐MS was furthermore used for research on the metabolism of microorganism , plants and mushroom . Additional publications are included in Table .…”
Section: Analytical Applicationsmentioning
confidence: 99%
“…Metabolic profiling was performed on rodent muscle , heart , liver , brain , intestinal and glioma tissue, arterial cells as well as on rodent serum/plasma , urine and feces . CE‐MS was furthermore used for research on the metabolism of microorganism , plants and mushroom . Additional publications are included in Table .…”
Section: Analytical Applicationsmentioning
confidence: 99%
“…Trehalose was reported as an essential energy source in filamentous fungi and yeast [ 66 ], and it has a key role during fermentation in Saccharomyces cerevisiae [ 67 ]. The metabolic profiling of three strains of Grifola frondosa showed that trehalose, glycerol, and glucose were the most abundant metabolites [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…The study revealed the role of brown mycelium in cell wall synthesis, light sensing, reduction of oxygen, and metabolic of carbohydrates [ 119 ]. Different cultivation components were compared during the cultivation of the edible mushroom Grifola frondosa (Maitake) CE–MS-based metabolomics study revealed differences in amino acid and organic acid in the strain GF433 with high amount compared to the stain Mori52, which may reveal high efficiency of the stain GF433 with high metabolite content and product efficiency [ 120 ]. Research conducted using a pea byproduct as a substrate for fungi growth with A. oryzae showed the highest ability to produce protein mass (54% of the total mass).…”
Section: Fungi As Protein and Carbohydrate Sourcementioning
confidence: 99%